On the benefit of a phenomenological revision of problem solving - Wendt, Alexander Nicolai (Journal of phenomenological psychology, 2017)
Problem solving has been empirical psychology's concern for half a century. Cognitive science's work on this field has been stimulated especially by the computational theory of mind. As a result, most experimental research originates from a mechanistic approach that disregards genuine experience. On the occasion of a review of problem solving's foundation, a phenomenological description offers fruitful perspectives. Yet, the mechanistic paradigm is currently dominant throughout problem solving's established patterns of description. The review starts with a critical historical analysis of the state of problem solving in academic psychology. Subsequently, a phenomenological, contrastive approach is proposed. It questions the notion of problems as "goal-driven" behavior by making vivid experience the subject of discussion. As its given compounds, solvability, oppressiveness, and the problem's horizon are discussed. Ultimately, an experience- based multimodal notion of the problem is elaborated that relates problems to challenges, fatalities and opportunities as different types of situations.